Changes in facial appearance alter one’s sensitivity not only to the self but also to the outside world - Honma, Motoyasu; Yoshiba, Sayaka; Miyamoto, Saya; Himi, Nanae; Haga, Shugo; Ogura, Sumire; Maki, Koutaro; Masaoka, Yuri; Izumizaki, Masahiko; Shirota, Tatsuo (Frontiers in Psychology, 2024)
Introduction Changes in facial appearance due to orthognathic surgery are known to improve a patient’s postoperative quality of life, however, potential changes in cognitive function are unknown. This study examined the effects of changes in facial appearance due to orthognathic surgery on the sensitivity to self and to outside objects in patients with jaw deformities. Methods Patients with jaw deformities (n = 22) and healthy controls (n = 30) were tested at 3 months preoperatively, at 1 month preoperatively, and at 1 month postoperatively to assess their impression of objects (positive, negative, and neutral pictures) and their evaluation of their own face and body. Results The results showed that changes in facial appearance improved self-evaluation and increased their sensitivity to emotional objects even when the objects were identical. Furthermore, the improving rating for own face was associated with the sensitivity for objects. Discussion The changes in facial appearance in patients may have helped to clear the sensitivity to these emotional objects. These findings may provide a new indicator of efficacy in orthognathic surgery.